Rising Tides - Roberts, Nora (New York Jove Books, 2002)
In response to his father's last wish, Ethan Quinn returns to the Maryland shore to care for Seth, a troubled boy in need of a family. Carrying on the family boatbuilding business, Ethan also finds the opportunity to reexamine his past.
Keywords: Brothers -- Atlantic Ocean--Chesapeake Bay -- Boatbuilding